2019
DOI: 10.51985/jbumdc2019107
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Priming Principle on Propofol Dose Required to Induce General Anesthesia

Abstract: Objective: To compare the mean induction dose of Propofol to induce general anesthesia by conventional method versus mean induction dose after applying priming principle. Study Design and Setting: Randomized controlled trial at Operation theatre complex, Shalamar Hospital, Lahore from November 2016 to May 2017. Methods: A total of 100 patients aged 18-55 years were equally divided into control and study groups. After standard anesthetic monitoring, intravenous propofol was used for induction of general anesthe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…21 Hamid and his colleagues tried to use the priming principle to decrease the induction dose of propofol because propofol dose increment is directly related to cardiovascular depression. 22 The incidence of post-induction hypotension was also studied recently in 2022 and it was concluded that induction with propofol & thiopental and orthopedics surgery are the independent risk factors for this hypotension. 23 The most remarkable finding of our study was the higher values of standard deviations in each comparison.…”
Section: Discussionmentioning
confidence: 99%
“…21 Hamid and his colleagues tried to use the priming principle to decrease the induction dose of propofol because propofol dose increment is directly related to cardiovascular depression. 22 The incidence of post-induction hypotension was also studied recently in 2022 and it was concluded that induction with propofol & thiopental and orthopedics surgery are the independent risk factors for this hypotension. 23 The most remarkable finding of our study was the higher values of standard deviations in each comparison.…”
Section: Discussionmentioning
confidence: 99%